Natural Fiber-based Green Composites: Processing, Properties and Biomedical Applications - Hoque, Md Enamul; Rayhan, Asif Mahmud; Shaily, Samira Islam (Applied Science and Engineering Progress, 2021)
Since the advent of modern technological civilization, tremendous pollution has been emerged in our environment by disposing of waste material in the environment unconsciously. Some waste materials are biodegradable and some of them are non-biodegradable. Biodegradable waste, originated from plants or animals, can be decomposed by the natural organism (bacteria, fungi, etc.) and can be excluded from pollution. This degradation process may be rapid or slow but the environmental risks are low. On the other hand, non-biodegradable waste, obtained from inorganic components cannot be decomposed by the natural organism and act as a source of pollution. These wastes are being generated by humans, and every year billions tons of wastes are being dumped into the environment which puts our environment in danger. As a result, environmental consciousness has increased worldwide. This growing ecological and environmental awareness leads the world to develop eco-friendly materials. As the population grows day by day, it is not possible to reduce waste. So, it is wise to focus on developing new materials that would produce biodegradable waste. Recently, the attraction on the biocomposite (known as green composites) materials has significantly increased because it is generated from natural fiber which is biodegradable and it has the potential of being a substitute for conventional non-biodegradable products. Biocomposites are used in various industrial sectors, including the bio-medical industry. In this paper, the overall idea of natural fibers, extraction and surface modification methods of natural fiber, natural fiber-based biocomposites, fabrication and properties analysis of biocomposite, and recent applications of biocomposites in the medical sector have been reviewed. The primary incentive for developing and using biocomposite is to build a new generation of eco-friendly materials by replacing synthetic ones.